1990
DOI: 10.1007/bf00045289
|View full text |Cite
|
Sign up to set email alerts
|

9-?-L(+) Adenosine: A new naturally occurring plant growth substance elicited by triacontanol in rice

Abstract: The naturally occurring plant growth substance elicited by triacontanol was found to be 9-#-L(+) adenosine by physical and spectral methods . At picomolar concentrations, 9-J3-L(+) adenosine stimulated growth as determined by dry weight measurements of several plant species . Reaction of adenosine deaminase with adenosine from rice showed that small quantities of 9-f-L(+) adenosine exist in plants . We believe this is the first report of 9-R-L(+) adenosine as a natural product .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 14 publications
(32 reference statements)
1
28
0
Order By: Relevance
“…The adenosine from TRIAtreated plants was identical to the adenosine obtained from control plants as determined by melting point, IR and MS, and from proton and carbon NMR analysis (Ries et al 1990). However, only the pure adenosine obtained from TRIA-treated plants could stimulate the plant growth.…”
Section: Tria Elicits L( )-Adenosinementioning
confidence: 75%
See 4 more Smart Citations
“…The adenosine from TRIAtreated plants was identical to the adenosine obtained from control plants as determined by melting point, IR and MS, and from proton and carbon NMR analysis (Ries et al 1990). However, only the pure adenosine obtained from TRIA-treated plants could stimulate the plant growth.…”
Section: Tria Elicits L( )-Adenosinementioning
confidence: 75%
“…TRIM has been identified as 9-b-l (')-adenosine (9H-purin-6-amine, 9-b-L-ribofuranosyl) as depicted in Figure 2. TRIA enhanced the formation or release of L(')-adenosine in the root tissue of rice seedlings within one min of TRIA application to the shoots, which might have elucidated the first step in the mode of TRIA action (Ries et al 1990). It is already reported that TRIA rapidly increases the ratio of l(')-adenosine to d(Á)-adenosine, probably at the tonoplast (Ries 1991).…”
Section: Mode Of Tria Actionmentioning
confidence: 78%
See 3 more Smart Citations